mtDNA analysis shows common ancestry in two kindreds with X-linked recessive hypoparathyroidism and reveals a heteroplasmic silent mutation. - Mumm, S; Whyte, M; Thakker, R; Buetow, K; Schlessinger, D (1997)
Two kindreds residing in eastern Missouri and exhibiting X-linked recessive idiopathic hypoparathyroidism have been described. Genealogical records extending back five generations revealed no common ancestor. To investigate the possibility of relatedness, the DNA sequence of the mitochondrial D-loop was compared among several individuals in both kindreds. The mtDNA D-loop was amplified from the total DNA of individuals by use of nested PCR reactions, and the resulting 430-bp fragment was sequenced. The mtDNA sequence was identical among affected males and their maternal lineage for individuals in both kindreds. Conversely, the mtDNA sequence of the fathers of the affected males differed from that of the maternal lineage at three to six positions. These results demonstrate that the two kindreds exhibiting X-linked recessive hypoparathyroidism are indeed related and that an identical gene defect is responsible for the disease. A further feature of the inheritance pattern was examined when a unique point mutation was identified in the mtDNA of one branch of one of the kindreds. This mutation appears to be de novo and segregates in subsequent generations without obscuring relatedness. In addition, the results of our study of mtDNA analysis indicate that this approach may be of importance in investigating common ancestry in other X-linked disorders.